2008
DOI: 10.1071/sr07223
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in soil respiration and temperature sensitivity under three land-use types in hilly areas of the Sichuan Basin

Abstract: CO 2 emissions from soils were measured under 3 land-use types at the adjacent plots of forest plantation, grassland, and cropland from January 2005 to December 2006. Mean soil CO 2 efflux rates measured during the 2-year study varied from 59 to 527 mg CO 2 /m 2 .h in forest plantation, 37 to 498 mg CO 2 /m 2 .h in grassland, and 32 to 397 mg CO 2 /m 2 .h in cropland. Soil respiration in the 3 types of land-use showed a similar seasonal pattern in variation during both years, in which the single-peaked curve o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 48 publications
6
15
1
Order By: Relevance
“…Both seasonal respiration quotient and Q 10 values at each measuring time indicates that soil CO 2 fluxes in both forest ecosystems are significantly sensitive to temperature. Previous studies have demonstrated that temperature sensitivity of soil respiration (Q 10 ) was affected negatively by soil temperature (Xu and Qi 2001;Wang et al 2008). Our results partly support this conclusion because Q 10 values were relatively small in summer compared with spring and autumn.…”
Section: Discussionsupporting
confidence: 82%
“…Both seasonal respiration quotient and Q 10 values at each measuring time indicates that soil CO 2 fluxes in both forest ecosystems are significantly sensitive to temperature. Previous studies have demonstrated that temperature sensitivity of soil respiration (Q 10 ) was affected negatively by soil temperature (Xu and Qi 2001;Wang et al 2008). Our results partly support this conclusion because Q 10 values were relatively small in summer compared with spring and autumn.…”
Section: Discussionsupporting
confidence: 82%
“…The high exponential positive correlation of R S with ST reported in this study indicates that R S was strongly influenced by seasonal temperature change for all three subalpine ecosystems. Similar findings have been reported in numerous previous studies on different ecosystems (Raich and Schlesinger 1992;Wang et al 2008;Yan et al 2009). The magnitude of temporal variation in R S due to ST varied from 55% at clear-cut land to 61% at primary forest (Table 3).…”
Section: Effects Of Soil Temperature and Soil Moisture On Soil Respirsupporting
confidence: 80%
“…Land use change effects on soil respiration have not been extensively studied (Carlisle et al 2006;Wang et al 2008), especially with respect to the change from agricultural to short-rotation (20 years or less) plantations as is found in our study area. Saurette et al (2008) found no effect on CO 2 emissions in 2006 in the first year after land use change from barley (Hordeum vulgare L.) to Walker poplar (Populus deltoides × Populus × petrowskyana var.…”
Section: Introductionmentioning
confidence: 90%